INNOVATIVE TECHNOLOGIES IN RO-RO TRANSPORT - Jurkovič, Martin; Sosedová, Jarmila (Doprava a spoje, 2012)
Design, technology and organisation are within the logistics chain important aspects to consider. Ro-Ro technologies used throughout multimodal logistic solutions are concepts that represent great potential in cost savings and lead-time reductions, compared to existing systems. Promoted different Ro-Ro technologies for vessels (Enisys) and terminal (Ipsi) also show how this technologies combined together can represent potential cost position and lead-time improvements for the logistic chain.